Indonesian Muslim Consumers’ Perceptions of Korean Halal Cosmetics - Khairuddin, Khairuddin; Asipah, Asipah; Dato' Md. ZIN, Onn (Jurnal Halal Center, 2026)
This research examines Indonesian Muslim consumers’ perceptions of halal Korean cosmetics amid the rapid expansion of the global K-beauty industry and the growing demand for halal-certified products. The research aims to analyse how the concept of halal is constructed, identify key factors shaping consumer perceptions, and assess the implications of these perceptions for consumption decisions. Employing a qualitative-dominant mixed-methods approach, the research combines semi-structured interviews with Indonesian Muslim consumers and survey data, which are analysed through thematic analysis and structural modelling. The findings reveal that consumers interpret halal cosmetics through three interrelated dimensions: ritual purity, ethical sourcing, and holistic wellness. Halal certification emerges as the primary trust anchor, while religiosity significantly moderates the formation of perceptions and purchase behaviour. Brand trust, Korean cultural appeal, and digital influencers further reinforce positive perceptions, whereas uncertainty regarding supply chain integrity generates perceived halal risk. The research concludes that perceptions of halal play a decisive role in shaping attitudes, loyalty, and identity negotiation among Indonesian Muslim consumers of Korean cosmetics. These findings contribute to the literature on halal consumer behaviour and provide strategic insights for cosmetic brands and policymakers seeking to strengthen trust and market acceptance in Muslim-majority contexts
Keywords: Array